SELF ESTEEM PARUH BAYA YANG GEMAR MEMBAWA BADIK (Studi Kasus pada 3 Orang Masyarakat Kabupaten Gowa) - S Abd Latief, Nurulsani (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
adik is a traditional weapon from South Sulawesi which has a meaning as a symbol of masculinity, self-confidence and a tool to become oneself. This study aims to determine the description of middle-aged self-esteem who like to carry a badik. This study uses a descriptive qualitative research method with a case study research type. The number of respondents in this study was 2 people and 1 respondent as data triangulation. This study uses data collection techniques, namely observation, interviews and documentation. Furthermore, the data analysis technique uses data reduction techniques, data presentation, data validation, conclusions and verification. The results of the study obtained are that middle-aged self-esteem increases when they carry a badik because by carrying a badik the respondent's self-confidence increases and this tool helps respondents protect themselves from danger.. Keyword : self esteem, dagger, middle age